2011
DOI: 10.1203/pdr.0b013e3182130c54
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Processing in Autism: A Review of Neurophysiologic Findings

Abstract: Atypical sensory-based behaviors are a ubiquitous feature of autism spectrum disorders (ASD). In this article, we review the neural underpinnings of sensory processing in autism by reviewing the literature on neurophysiological responses to auditory, tactile, and visual stimuli in autistic individuals. We review studies of unimodal sensory processing and multi-sensory integration that use a variety of neuroimaging techniques, including: electroencephalography (EEG), magnetoencephalography (MEG), and functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

28
642
2
19

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 837 publications
(691 citation statements)
references
References 98 publications
28
642
2
19
Order By: Relevance
“…Alterations in sensory processing constitute prominent symptoms in various psychiatric disorders (e.g., autism, schizophrenia, and personality disorders) (50)(51)(52)(53). While genetic alterations are considered to be important as etiologies of these mental illnesses, postnatal environment could also contribute to the onset of these mental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in sensory processing constitute prominent symptoms in various psychiatric disorders (e.g., autism, schizophrenia, and personality disorders) (50)(51)(52)(53). While genetic alterations are considered to be important as etiologies of these mental illnesses, postnatal environment could also contribute to the onset of these mental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…These affect a broad range of skills ranging from social to mental-cognitive ones (Wing & Gould, 1979), and to perceptual and sensory abnormalities (Klintwall et al, 2011;Marco, Hinkley, Hill, & Nagarajan, 2011). That lack of motor movement and correlated motor-andsensory neural activity can entail deficits in integrating perceptions with actions is well known from experimental studies dating back to the famous work by Heid and Hein (1963), and some of the perceptual problems in ASC seem open to this explanation (e.g., inadequate response to social stimuli).…”
mentioning
confidence: 99%
“…Klin et al's account spoke of the grounding of social processes in experience, but did not strongly highlight the necessary integrity of motor and sensory systems along with their structural connection for the typical development of thought and social behaviour. At the time, much less was known about fundamental dysfunction in sensorimotor and neuronal systems in ASC, such as the motor abnormalities that have been outlined in Sections 2 and 3 above or the sensory abnormalities that are the focus of other papers (Klintwall et al, 2011;Marco et al, 2011).…”
mentioning
confidence: 99%
“…For example, age and IQ level have been shown to affect frequency discrimination (Heaton, Williams, Cummins and Happé, 2008; in ASD. Another explanation for the discrepancy in findings may be due to the considerable variation in paradigms used (Marco, Hinkley, Hill and Nagarajan, 2011). Auditory perceptual abilities in ASD may depend on the nature and complexity of the stimulus and the task (Bertone Mottron, Jelenic, and Faubert 2005;Samson et al, 2006;Mongillo et al, 2008).…”
mentioning
confidence: 99%
“…More importantly, the relationship between auditory processing and autistic symptomatology is far from complete. It has been suggested that future research employing correlational analyses between auditory perceptual abilities and behavioural phenotypes could help to clarify the inconsistencies in the findings (e.g., Marco et al, 2011).…”
mentioning
confidence: 99%